Researching the Information Commons (RIC) - Smith, Kerry (International Federation of Library Associations and Institutions (IFLA), 2010)
There was a time when working in the information industry as known to libraries was relatively predictable as far as information policy issues were concerned. We espoused the public good philosophies of our professional bodies with regard to issues including freedom of information, information access and delivery, information ownership, copyright and user privacy. Then came the Internet. There is no doubt that the Internet has provided new information issues and challenges that are being encountered, and these need to be addressed, and not only in the law courts. One all embracing issue is that of the new place of information in a commons environment. The pragmatic members of the library profession have grasped the commons concept and made their libraries an "information commons" but who has really challenged and thought through in a research sense, the issues that surround the commons provision of information; a concept dear to the hearts of many of the world's librarians?This question lead to the development of a researcher networking initiative, represented on the Web as Researching the Information Commons (RIC) http://infocommons.curtin.edu.au The website has a growing number of participants, not all working together, but who are interested in information commons matters from a research points of view. The vision for the RIC Group is to nurture and mentor a community of researchers interested in matters relating to the information commons, by being in itself an information commons. It will operate through: openness and feedback; shared decision making; diversity within the commons; honouring social and legal equity amongst its members; and fostering sociability within the commons (from Bollier, 2004, p.275). The paper will outline the thinking behind RIC, the work of its members and some hopes for the future.